Characterization of 12 Novel Microsatellite Markers of Sogatella furcifera (Hemiptera: Delphacidae) Identified From Next-Generation Sequence Data. Issue 1 (9th July 2015) - Nam, Hwa Yeun; Coates, Brad; Kim, Kyung Seok; Park, Marana; Lee, Joon-Ho
Abstract : The white-backed planthopper, Sogatella furcifera (Horváth) (Hemiptera: Delphacidae), is a major pest of rice and has long-range migratory behavior in Asia. Microsatellite markers (simple sequence repeats) have been widely used to determine the origins and genetic diversity of insect pests. We identified novel microsatellite loci for S. furcifera samples collected from Laos, Vietnam, and three localities in Bangladesh from next-generation Roche 454 pyrosequencing data. Size polymorphism at 12 microsatellite loci was verified for 40 adult individuals collected from Shinan, South Korea. The average number of alleles per locus was 7.92. The mean values of observed ( H o ) and expected heterozygosities ( H E ) were 0.615 and 0.757, respectively. These new microsatellite markers will be a resource for future ecological genetic studies of S. furcifera samples across more broad geographic regions in Asia and may assist in estimations of genetic differentiation and gene flow among populations for implementation of more effective management strategies to control this serious rice pest.